Biotecnologias e super-heróis: aproximações pós-humanistas - Cardoso, Pablo Ribeiro (2018)
This research has as its main objective to discuss overcoming the organic limits of the body through biotechnological interventions, taking as basis the superhero characters. Starting from the field of changes in the biopowers listed by Nikolas Rose and the anthropogenic effects of biotechnologies, it initially seeks to understand the emergence of the posthuman concept and how it implies new ways of thinking the body in the contemporary, especially from the proposals for human enhancement. The posthuman is thought of as an umbrella term to refer to a variety of different movements and schools of thought, including scientific, philosophical, artistic, and mystical discussions of the most varied aspects. Aiming to offer contributions on the subject, contemporary projects of human enhancement through biomedical/biotechnology paths are studied, thus excluding from this research transcendental approaches or the ones that preach the total substitution of the biological body for digital. Once these projects have been explored, based on Lucia Santaella's conceptualization of prostheses, ways of overcoming the limits of the human body through biotechnological interventions are discussed, with biotechnological hybridization of the new prostheses as the main focus. Choosing superheroes as interlocutors in this debate, the research rescues their historical and social backgrounds, delineates who these characters are, and analyze the bodies portrayed by them, named by Scott Jeffery as superhuman bodies. It explores, therefore, the different ways in which superheroes illustrate the idea of an improved human body. Finally, to support the role of superheroes as basis of the discussions proposed in the research, the text dialogues with descriptions of adventures and images from comic books or films which these characters are the protagonists